Analysis of features of recombination mechanisms in silicon solar cells - Korkishko, R.M.; Kostylyov, V.P.; Prima, N.A.; Sachenko, A.V.; Serba, O.A.; Slusar, T.V.; Chernenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Investigated in this paper are theoretical and experimental spectral
dependences of the short-circuit current as well as small-signal photo-e.m.f. in silicon
solar cells. The authors have considered two constructions of solar cells. The first
construction is a solar cell with contacts on the front and back surfaces, and the second –
solar cells with back barriers and contact metallization. Analyzed in the work are spectral
dependences of the internal quantum efficiency for the short-circuit current and smallsignal
photo-e.m.f.
It has been shown that the short-wave drop of the short-circuit current is related with
recombination on deep centers at the front surface as well as inter-band Auger
recombination in the heavily doped emitter. At the same time, availability of the shortwave
drop in the small-signal photo-e.m.f. is related with limitation of the efficient rate
of surface recombination Seff(l) due to diffusion inflow.
The latter takes place when a layer with the thickness dp and increased recombination is
available near illuminated surface. In this case, the mechanism providing decrease in the
small-signal photo-e.m.f. in the area of strong light absorption is related with increasing
the efficient rate of surface recombination near the front surface, when the dominant
amount of electro-hole pairs is generated in the layer with the increased recombination
rate. The same mechanism is responsible for the short-circuit current drop in solar cells
with back barriers and contact metallization.
Juxtaposition of theoretical and experimental results enabled to determine parameters
that characterize sub-surface properties of solar cells, namely: the thickness of the
surface layer with increased recombination, lifetime of carriers in it, and dependences
Seff(l).